Reclaiming Jakarta North Coast: Perspective from Defense, Security and Constitutional Aspects - Setiawati, Vera Wheny (UI Scholars Hub, 2018)
Indonesia defines itself as a maritime country, since its territory consists of four-fifth sea and only one-fifth land. Indonesia’s sea territory is particularly important in uniting the country, as the sea is a medium for interconnectivity, national integrity, resources, diplomacy, national defense and security. This paper will focus on the sea’s significance to Indonesia’s national unity in its role as a medium for interconnecting the country’s many islands, and the implications thereof to Indonesia’s national security and defense. This paper will discuss within this context in particular the reclamation of Jakarta’s north coast, the 32-kilometer coastline of Indonesia’s capital city. The reclamation project will reclaim a total of 27,000 hectares of land, and privatize the whole extent of Jakarta’s coastline, which serves as the city’s gateway to the sea. This paper will thus examine how to negotiate the various political, economic, social and cultural interests within the reclamation project, and address issues regarding national defense and security arising from the project. This research applies a normative empirical methodology, and intends to provide a scientific basis for the argument that as Jakarta’s coastline is crucial in terms of national defense and security matters, the coastline should therefore be managed by a state agency and remain publicly accessible.